PENYELESAIAN SENGKETA KETENAGAKERJAAN TERKAIT UPAH PEKERJA PT AUDIKA JAYA BERSAMA YANG TIDAK DIBAYARKAN OLEH PT PERKEBUNAN NUSANTARA VII (Studi Putusan Nomor 19/Pdt.G/2024/PN Tjk) - Fathaniah Ghaisani Putri; Zulfi Diane Zaini (INTELIGENSIA MEDIA, 2026)
One of the issues that often stands out in employment is disputes related to wage payments. In many cases, workers face a situation where the wages they should receive are not paid by the company. This is not only financially detrimental to workers, but can also have broader social impacts, including dissatisfaction among workers and potential conflict between workers and the company. The research method used in this study is through a normative and empirical legal approach using secondary and primary data. The purpose of this study is to determine the factors causing the occurrence of labor disputes related to the wages of PT Audika Jaya Bersama workers that were not paid by PT Perkebunan Nusantara and the process of resolving disputes related to the wages of PT Audika Jaya Bersama workers that were not paid by PT Perkebunan Nusantara VII. The results of this study indicate that one of the main causes of the dispute between PT Audika Jaya Bersama and PT Perkebunan Nusantara VII is the ambiguity in the employment contract agreement, and the mediation process carried out in this case proves that resolving labor disputes through non-litigation channels is an effective and efficient step. Mediation provides space for both parties to dialogue, seek mutually beneficial solutions, and resolve conflicts peacefully.